Environmental justice in America : a new paradigm - Rhodes, Edwardo Lao, 1946- (Indiana University Press, 2003)
Rhodes examines the issue of environmental justice as a public policy concern and suggests the use of a new methodology in its evaluation. Rather than argue the merits of growth versus environmental protection, he makes the case that race and class were not major concerns of environmental policy until the 1990s. Although the volume deals primarily with the United States, it raises issues of international concern.